Building up Strain in One Step: Synthesis of an Edge‐Fused Double Silacyclobutene from an Extensively Trichlorosilylated Butadiene Dianion. Issue 37 (29th June 2020) - Georg, Isabelle; Bursch, Markus; Stückrath, Julius B.; Alig, Edith; Bolte, Michael; Lerner, Hans‐Wolfram; Grimme, Stefan; Wagner, Matthias
Abstract: The exhaustive trichlorosilylation of hexachloro‐1, 3‐butadiene was achieved in one step by using a mixture of Si2 Cl6 and [ n Bu4 N]Cl (7:2 equiv) as the silylation reagent. The corresponding butadiene dianion salt [ n Bu4 N]2 [1 ] was isolated in 36 % yield after recrystallization. The negative charges of [1 ] 2− are mainly delocalized across its two carbanionic (Cl3 Si)2 C termini (α‐effect of silicon) such that the central bond possesses largely C=C double‐bond character. Upon treatment with 4 equiv of HCl, [1 ] 2− is converted into neutral 1, 2, 3, 4‐tetrakis(trichlorosilyl)but‐2‐ene, 3 . The Cl − acceptor AlCl3, induces a twofold ring‐closure reaction of [1 ] 2− to form a six‐membered bicycle 4 in which two silacyclobutene rings are fused along a shared C=C double bond (84 %). Compound 4, which was structurally characterized by X‐ray crystallography, undergoes partial ring opening to a monocyclic silacyclobutene 2 in the presence of HCl, but is thermally stable up to at least 180 °C. Abstract : Upcycling : A sixfold trichlorosilylated butadiene dianion is accessible in one step from hexachlorobutadiene and the Si2 Cl6 /Cl − system. Cl − abstraction with AlCl3 causes a double cyclization reaction and quantitatively forms a six‐membered double silacyclobutene.